CHEMICAL CHARACTERIZATION AND BIOLOGICAL ACTIVITIES OF EXTRACTS OFTHREE PLANTS USED IN TRADITIONAL MEDICINE IN BENIN: TECTONA GRANDIS, UVARIA CHAMEAE AND JUSTICIA SECUNDA - Moukimou L, Akibou Osseni; Pascal, Agbangnan DC; Annick, Bossou; Yaya, Koudoro; Pierre, Noudogbessi A Jean; FELICIEN, AVLESSI; Dominique, Sohounhloue KC (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The present study was devoted to the chemical analysis of three plants (Tectona grandis, Uvaria chameae and Justicia secunda) usually used by traditional healers in Benin, for their curative properties in the treatment of certain diseases. Methods: After characterization of large chemical groups present in ethanolic extract of these plants, the total polyphenols were measured by the Folin method, the content of condensed tannins, total flavonoids, anthocyanins and anthocyanidins was evaluated by spectrophotometry. Results: The results show the presence of several secondary metabolites such as saponins, alkaloids, tannin, mucilages, anthraquinones, leucoanthocyanins, anthocyanins and triterpene in varying proportions in the three plants. The contents of condensed tannins, of anthocyanidins, total polyphenols and total flavonoids are respectively higher in the leaves (13.409 mg/g, 1.529 mg/g, 3.479 mg/g and 24.640 mg/g) than the bark of T.g (8.612 mg/g, 0 mg/g, 2.694 mg/g and 12.410 mg/g). As against, leaves of U.care richer in condensed tannins, flavonoids and total polyphenols (44.290 mg/g, 9.135 mg/g, 4.779 mg/g) than J.s (0 mg/g, 2.011 mg/g and 1.478 mg/g) unlike anthocyanidins. Of three plants studied, U.c was revealed the richest in polyphenolic compounds (condensed tannins, total polyphenols) and J.s was least rich. This content of polyphenolic compounds explain the antiradical activities observed; an CI50 of 0.700 mg/mL for U.c, 14.340 mg/mL for leaves of T.g, 24.790 mg/mL for bark of T.g and 46.500 mg/mL for leaves of J.s. Conclusion: This study contributes to increase those plants's phytochemical knowledge and allows having a better understanding of their pharmacological properties Keywords: Polyphenols, Antiradical activities, Solid phase micro extraction, Tectona grandis, Uvaria chameae, Justicia secunda.